Hybridization-based detection of Helicobacter pylori at human body temperature using advanced Locked Nucleic Acid (LNA) probes - Sílvia Fontenete (2013)
The understanding of the human microbiome and its influence upon human life has long been a subject of study. Hence, methods that allow the direct detection and visualization of microorganisms and microbial consortia (e. g. biofilms) within the human body would be invaluable. In here, we assessed the possibility of developing a variant of fluorescence in situ hybridization (FISH), named fluorescence in vivo hybridization (FIVH), for the detection of Helicobacter pylori. Using oligonucleotide variations comprising locked nucleic acids (LNA) and 2'-O-methyl RNAs (2'OMe) with two types of backbone linkages (phosphate or phosphorothioate), we were able to successfully identify two probes that hybridize at 37 degrees C with high specificity and sensitivity for H. pylori, both in pure cultures and in gastric biopsies. Furthermore, the use of this type of probes implied that toxic compounds typically used in FISH were either found to be unnecessary or could be replaced by a non-toxic substitute. We show here for the first time that the use of advanced LNA probes in FIVH conditions provides an accurate, simple and fast method for H. pylori detection and location, which could be used in the future for potential in vivo applications either for this microorganism or for others.